Silicon negative electrode material and preparation method and application thereof
By designing a dual continuous network structure composed of silicon and carbon, the problems of conductive network damage and SEI film rupture caused by volume changes in silicon-based anode materials in lithium-ion batteries are solved. The silicon anode material is coated with amorphous carbon to achieve high performance The negative electrode of lithium-ion battery avoids the use of toxic chemical reagents and expensive raw materials.
Patent Information
- Application Number
- CN202411353081.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon-based anode materials have problems such as volume changes in lithium-ion batteries, resulting in electrical conduction network damage, SEI film rupture and electrolyte consumption, and the use of toxic chemical reagents and expensive raw materials limits the production of mesoporous silicon anodes.
Using a dual continuous network structure composed of silicon and carbon, the silicon negative electrode material is coated with amorphous carbon, through the heating reaction of mesoporous silica aerogel, magnesium powder and sodium chloride, combined with carbonization of high-temperature asphalt, and finally coated with amorphous carbon. A Si/C composite material was designed to overcome volume changes and improve electrochemical properties.
A high initial discharge capacity and reversible capacity are achieved, providing good electron and ion transport channels, reducing resistance and polarization of electrode materials, improving cycle stability and reducing electrolyte consumption.
Smart Images

Figure CN119170774A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a silicon negative electrode material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the booming development of the electric vehicle industry, the existing negative electrode material system is difficult to meet the requirements of higher energy density (>300Wh / kg) of lithium-ion batteries. Silicon-based negative electrodes have high energy density, high theoretical specific capacity (about 4200mAh / g), low discharge potential (compared to Li / Li + Compared with the negative electrode material, it has the advantages of low voltage (<0.4V) and abundant resources, and is considered to be one of the most promising materials to replace graphite negative electrodes.
[0004] However, the main challenges of silicon-based negative electrodes are as follows: (1) Embedding a large amount of lithium in the silicon atomic lattice will cause a 300% volume change in the silicon itself, which will lead to the pulverization of the silicon material; (2) During the lithium insertion and delithiation process of the silicon material, the repeated changes in the volume of the active material will cause the conductive network of the silicon negative electrode to be destroyed and collapsed, and lose electrical contact with the current collector, resulting in unstable electrochemical performance of the silicon negative electrode; (3) Due to the huge volume change of the silicon negative electrode during the charge and discharge process, the solid electrolyte interface SEI film is easily broken, and the SEI film will be regenerated on the silicon electrode surface exposed to the electrolyte, which will lead to continuous consumption of the electrolyte and the formation of a thick and uneven SEI film, and ultimately cause a loss of specific capacity.
[0005] In response to the above technical problems, the prior art has obtained silicon materials with various nanostructures, such as nanoparticles, nanowires, nanotubes, nanosheets and porous nanostructures, by nanosizing silicon. These nanostructures can adapt to huge volume changes, which is conducive to accelerating the electrochemical reaction rate of silicon-lithium. However, for particles of different sizes, the absolute volume after expansion is different at the same volume expansion rate. Therefore, designing a porous structure for silicon materials is a very promising method. The advantages of this structure are: (1) sufficient pores provide a Si expansion zone during the buffer cycle; (2) the transport route of lithium ions and electrons can be greatly shortened; (3) the reactants can be fully contacted.
[0006] There are two main modes of composite silicon-based porous negative electrode materials currently used: one is as shown in patent CN117446806A, in which ferrosilicon powder is first added to dilute hydrochloric acid for soaking and stirring to obtain partially dealloyed ferrosilicon powder, and then the powder is placed in a mixed solution of hydrofluoric acid and hydrogen peroxide, stirred for reaction, filtered and dried to obtain a silicon-based porous negative electrode material; the other is as shown in patent CN116154141A, in which silicon nanowire material is used as the active material of the negative electrode sheet and is matched with a specific binder to improve the energy density and cycle performance of the lithium battery.
[0007] However, the inventors have found the following problems in the prior art: the use of toxic chemical reagents (such as hydrofluoric acid) and expensive raw materials (such as silicon powder, silicon nanowires) will limit the production of mesoporous silicon negative electrodes to a certain extent. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a silicon negative electrode material and a preparation method and application thereof, which specifically adopts the following technical solutions:
[0009] According to a first aspect of the present invention, a silicon negative electrode material is provided, wherein the silicon negative electrode material comprises a composite material composed of silicon and carbon, wherein the silicon and carbon are interspersed with each other to form a continuous network structure, and the outer layer is coated with amorphous carbon.
[0010] The second aspect of the present invention provides a method for preparing the above silicon negative electrode material, comprising the following steps:
[0011] S1, adding a soluble silicate solution into dilute hydrochloric acid to form a wet gel, then performing a hydrolysis reaction and a gelation reaction, and performing a solvent exchange on the obtained gelation system to obtain a mesoporous silica aerogel;
[0012] S2, mixing mesoporous silica aerogel, magnesium powder and sodium chloride and heating them to react to obtain mesoporous silica;
[0013] S3, impregnating the mesoporous silicon with high-temperature asphalt and then carbonizing it to obtain a bicontinuous Si / C composite negative electrode material;
[0014] S4. A carbon source gas is introduced into the bicontinuous Si / C composite negative electrode material to obtain an outer layer amorphous carbon-coated silicon negative electrode material after reaction.
[0015] As a further technical solution, in step S1, the soluble silicate solution is a sodium silicate solution; the sodium silicate solution is obtained by stirring a sodium silicate aqueous solution with a mass fraction of 35-45% and deionized water at room temperature until they are uniformly mixed; the volume ratio of the sodium silicate aqueous solution to the deionized water is 1:1-1:2; the volume ratio of the sodium silicate aqueous solution, deionized water and dilute hydrochloric acid is 2-4:3-5:4-6; the concentration of the dilute hydrochloric acid is 1-5 mol / L.
[0016] As a further technical solution, the volume ratio of the sodium silicate aqueous solution to deionized water is 3:4; the volume ratio of the sodium silicate aqueous solution, deionized water and dilute hydrochloric acid is 3:4:5; and the concentration of the dilute hydrochloric acid is 3 mol / L.
[0017] As a further technical solution, in step S1, the reaction temperatures of the hydrolysis reaction and the gelation reaction are both 55-75° C., and the reaction times are both 1.5-2.5 h.
[0018] As a further technical solution, the reaction temperature of the hydrolysis reaction and the gelation reaction are both 65° C., and the reaction time is both 2 hours.
[0019] As a further technical solution, in step S1, a standing reaction is required after the gelation reaction to enhance the network structure of the gel.
[0020] As a further technical solution, the temperature of the static reaction is 55-75° C., and the reaction time is 22-26 hours.
[0021] As a further technical solution, the temperature of the static reaction is 65° C. and the reaction time is 24 hours.
[0022] As a further technical solution, in step S1, the solvent used in the solvent exchange is ethanol.
[0023] As a further technical solution, the solvent exchange needs to be performed 4 to 6 times, with an interval of 22 to 26 hours each time, to ensure that the hydrochloric acid and water in the pores are completely replaced by ethanol.
[0024] As a further technical solution, the solvent exchange needs to be performed 5 times, with an interval of 24 hours between each times.
[0025] As a further technical solution, in step S1, the drying method is supercritical drying.
[0026] As a further technical solution, in step S2, the weight ratio of the mesoporous silica aerogel, magnesium powder and sodium chloride is 0.8-1.2:0.8-1.2:8-12.
[0027] As a further technical solution, the mass ratio of the mesoporous silica aerogel, magnesium powder and sodium chloride is 1:1:10.
[0028] As a further technical solution, in step S2, the temperature of the heating reaction is 620-660°C, and the reaction time is 6-18 hours; the heating reaction is under argon atmosphere.
[0029] As a further technical solution, the temperature of the heating reaction is 650° C. and the reaction time is 12 hours.
[0030] As a further technical solution, in step S2, the heated product needs to be removed from impurities, cleaned and vacuum dried in sequence to obtain mesoporous silicon;
[0031] Wherein, the heated product is immersed in a 3M hydrochloric acid solution to remove by-products;
[0032] The vacuum drying temperature is 75-85°C.
[0033] As a further technical solution, the vacuum drying temperature is 80°C.
[0034] As a further technical solution, in step S3, the mass ratio of the mesoporous silica to the high-temperature asphalt is 0.8-1.2:0.8-1.2.
[0035] As a further technical solution, the mass ratio of the mesoporous silica to the high-temperature asphalt is 1:1.
[0036] As a further technical solution, in step S3, the heating treatment is divided into a first heating treatment and a second heating treatment;
[0037] The first heating treatment is to heat the temperature to 250-350°C at a heating rate of 3-8°C / min and keep the temperature for 20-40min to allow the molten graphene to penetrate into the pores;
[0038] The second heating treatment is to continue heating to 500-800° C. at a heating rate of 3-8° C. / min to pyrolyze the graphene into carbon, and the heat preservation time is 0.5-2 h.
[0039] As a further technical solution, the first heating treatment is to heat the temperature to 300°C at a heating rate of 5°C / min and keep the temperature for 30min;
[0040] The second heating treatment is to continue heating to 700° C. at a heating rate of 5° C. / min and keep the temperature for 1 hour.
[0041] As a further technical solution, before the heating treatment, argon gas is introduced at a flow rate of 1.4 to 3 L / min.
[0042] As a further technical solution, in step S4, the carbon source gas is selected from one or two of methane, ethylene or acetylene gas (purity 99.99%).
[0043] The third aspect of the present invention provides an application of the silicon negative electrode material prepared by the above method in a lithium ion battery.
[0044] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0045] (1) The present invention explores the best process for retaining the mesoporous structure by changing the magnesium thermal reduction time, thereby overcoming the problem that the prior art uses toxic chemical reagents and expensive raw materials to limit the production efficiency of the mesoporous silicon negative electrode.
[0046] (2) Thanks to the design of the dual-continuous structure, the Si / C anode of the present invention exhibits excellent electrochemical properties and has the potential to meet the requirements of high-performance lithium-ion battery negative electrodes.
[0047] (3) The Si / C composite material with a dual continuous structure prepared by the present invention has a high initial discharge capacity and a reversible capacity, which is due to the fact that the material realizes a uniform distribution of silicon material and carbon material with a high specific surface area, thereby providing more space for storing lithium ions.
[0048] (4) The Si / C composite material with a bicontinuous structure prepared by the present invention can maintain a high discharge capacity at a high rate because the material provides a good electron and ion transmission channel, thereby reducing the resistance and polarization phenomenon of the electrode material.
[0049] (5) The Si / C composite material with a dual continuous structure prepared by the present invention has good cycle stability, which is due to the fact that the material effectively solves the volume expansion problem of silicon material during the cycle and reduces the direct contact between silicon and electrolyte, thereby reducing the consumption of electrolyte during the silicon negative electrode cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0051] Figure 1 A schematic diagram of the structural changes of materials in the process of preparing a silicon-based negative electrode material provided by the present invention, wherein 1 is a mesoporous silica aerogel, 2 is mesoporous silicon, 3 is a bicontinuous Si / C composite negative electrode material, and 4 is an outer layer of amorphous carbon-coated silicon negative electrode material;
[0052] Figure 2 This is a scanning electron microscope image of the silicon-based negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0053] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0054] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0055] Embodiment 1 :This embodiment provides a method for preparing a silicon negative electrode material
[0056] (1) Weighing chemicals and reagents: The chemicals and reagents used include sodium silicate (Na2O·nSiO2), anhydrous ethanol (AR), hydrochloric acid (HCl), sodium chloride (NaCl), magnesium powder (Mg) and high-temperature asphalt. These chemicals and reagents are used to synthesize Si / C composite anode materials.
[0057] (2) Synthesis of mesoporous silica aerogel: First, dilute 30 mL of sodium silicate in 40 mL of deionized water and stir for half an hour to form a clear solution. Then, quickly add the solution to 50 mL of dilute hydrochloric acid and continue stirring for 30 minutes to form a uniformly dispersed wet gel. Perform hydrolysis and gelation reactions at 65°C for 2 hours to strengthen the network structure of the gel. Then, perform solvent replacement five times, each with an interval of 24 hours, to ensure that the hydrochloric acid and water in the pores are completely replaced by ethanol. Finally, the wet gel is supercritically dried to obtain mesoporous silica aerogel.
[0058] (3) Synthesis of mesoporous silicon (m-Si): Mesoporous silica aerogel was uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:1:10. The mixture was ground into fine powder and placed in a corundum boat and heated at 650°C in an argon atmosphere for 6 hours. The product was soaked in a 3M hydrochloric acid solution to remove by-products, washed three times with deionized water, and then dried in vacuum at 80°C.
[0059] (4) Preparation of bicontinuous Si / C composite anode material: The mesoporous silicon is further impregnated with high-temperature asphalt, and then the asphalt is carbonized into carbon to construct a bicontinuous Si / C composite anode material.
[0060] (5) Preparation of outer amorphous carbon coating: Place the product in a CVD rotary furnace, introduce carbon source gas, and turn off the power after the reactor runs for a period of time, and collect the product m-Si-6 in the collection chamber.
[0061] Embodiment 2 :This embodiment provides a method for preparing a silicon negative electrode material
[0062] (1) Weighing chemicals and reagents: The chemicals and reagents used include sodium silicate (Na2O·nSiO2), anhydrous ethanol (AR), hydrochloric acid (HCl), sodium chloride (NaCl), magnesium powder (Mg) and high-temperature asphalt. These chemicals and reagents are used to synthesize Si / C composite anode materials.
[0063] (2) Synthesis of mesoporous silica aerogel: First, dilute 30 mL of sodium silicate in 40 mL of deionized water and stir for half an hour to form a clear solution. Then, quickly add the solution to 50 mL of dilute hydrochloric acid and continue stirring for 30 minutes to form a uniformly dispersed wet gel. Perform hydrolysis and gelation reactions at 65°C for 2 hours to strengthen the network structure of the gel. Then, perform solvent replacement five times, each with an interval of 24 hours, to ensure that the hydrochloric acid and water in the pores are completely replaced by ethanol. Finally, the wet gel is supercritically dried to obtain mesoporous silica aerogel.
[0064] (3) Synthesis of mesoporous silicon (m-Si): Mesoporous silica aerogel was uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:1:10. The mixture was ground into fine powder and placed in a corundum boat and heated at 650°C in an argon atmosphere for 12 hours. The product was soaked in a 3M hydrochloric acid solution to remove by-products, washed three times with deionized water, and then vacuum dried at 80°C.
[0065] (4) Preparation of bicontinuous Si / C composite anode material: The mesoporous silicon is further impregnated with high-temperature asphalt, and then the asphalt is carbonized into carbon to construct a bicontinuous Si / C composite anode material.
[0066] (5) Preparation of outer amorphous carbon coating: Place the product in a CVD rotary furnace, introduce carbon source gas, and turn off the power after the reactor runs for a period of time, and collect the product m-Si-12 in the collection chamber.
[0067] Embodiment 3 :This embodiment provides a method for preparing a silicon negative electrode material
[0068] (1) Weighing chemicals and reagents: The chemicals and reagents used include sodium silicate (Na2O·nSiO2), anhydrous ethanol (AR), hydrochloric acid (HCl), sodium chloride (NaCl), magnesium powder (Mg) and high-temperature asphalt. These chemicals and reagents are used to synthesize Si / C composite anode materials.
[0069] (2) Synthesis of mesoporous silica aerogel: First, dilute 30 mL of sodium silicate in 40 mL of deionized water and stir for half an hour to form a clear solution. Then, quickly add the solution to 50 mL of dilute hydrochloric acid and continue stirring for 30 minutes to form a uniformly dispersed wet gel. Perform hydrolysis and gelation reactions at 65°C for 2 hours to strengthen the network structure of the gel. Then, perform solvent replacement five times, each with an interval of 24 hours, to ensure that the hydrochloric acid and water in the pores are completely replaced by ethanol. Finally, the wet gel is supercritically dried to obtain mesoporous silica aerogel.
[0070] (3) Synthesis of mesoporous silicon (m-Si): Mesoporous silica aerogel was uniformly mixed with magnesium powder and sodium chloride in a mass ratio of 1:1:10. The mixture was ground into fine powder and placed in a corundum boat and heated at 650°C in an argon atmosphere for 18 hours. The product was soaked in a 3M hydrochloric acid solution to remove by-products, washed three times with deionized water, and then dried in vacuum at 80°C.
[0071] (4) Preparation of bicontinuous Si / C composite anode material: The mesoporous silicon is further impregnated with high-temperature asphalt, and then the asphalt is carbonized into carbon to construct a bicontinuous Si / C composite anode material.
[0072] (5) Preparation of outer amorphous carbon coating: Place the product in a CVD rotary furnace, introduce carbon source gas, and turn off the power after the reactor runs for a period of time, and collect the product m-Si-18 in the collection chamber.
[0073] Comparative Example 1
[0074] This comparative example provides a silicon nanowire negative electrode sheet, which includes carbon-coated silicon nanowires, PR-PAA polymer materials, single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black (SuperP Li) and sodium carboxymethyl cellulose (CMC), wherein the PR-PAA polymer material has a telescopic function; the carbon-coated silicon nanowires have a diameter of 50 to 500 nm, a length of 5 to 100 μm, and a carbon content of 3 wt%; the preparation method of the silicon nanowire negative electrode sheet includes the following steps:
[0075] (1) The carbon-coated silicon nanowires were acid-washed with 10% hydrochloric acid, washed with deionized water for 8 times, heated at 500° C., evacuated, and then introduced with argon gas for gas replacement purification, and then ball-milled and dispersed to complete the pretreatment, thereby obtaining the pretreated carbon-coated silicon nanowires;
[0076] (2) using deionized water as a dispersing solvent, mixing single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black, CMC, PR-PAA polymer material and the carbon-coated silicon nanowires pretreated in step (1) to prepare a negative electrode slurry with a solid content of 8 wt %, extruding and double-sidedly coating the negative electrode slurry on a copper foil with a thickness of 7 μm, and after rolling, die-cutting, deburring, dust removal and pre-lithiation steps, obtaining the silicon nanowire negative electrode sheet;
[0077] The mass ratio of the carbon-coated silicon nanowires, single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon black, CMC and PR-PAA polymer material is 80:0.5:3:6.5:2:8.
[0078] Test example
[0079] The silicon negative electrode materials provided in Examples 1 to 3 and Comparative Example 1 are used to prepare a battery, and the specific steps include:
[0080] The electrochemical test was performed by assembling a CR2032 button battery, using Canrd 2500 as a separator, and the electrolyte formula was 1.0M LiPF6 in a 1:1:1 (volume ratio) mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), with 5wt% of fluoroethylene carbonate (FEC). The electrode slurry was prepared by mixing 96% of active material (50% each of silicon and carbon), 1% of conductive agent (carbon nanotubes) and 3% of binder (lithiated polyacrylic acid) with sufficient deionized water. The electrode slurry was evenly coated on the copper foil and then dried in a vacuum oven at 105°C for 6 hours. The coating thickness was 100μm to maintain uniform mass loading. The comparison results of the physical properties of the embodiments and comparative examples are shown in Table 1:
[0081] Table 1 Comparison of physical properties of the embodiments and comparative examples
[0082]
[0083] It can be seen from Table 1 that the first charge and discharge capacity of the silicon-carbon negative electrode materials prepared in Examples 1 to 3 is better than that in Comparative Example 1. This is because the bicontinuous structure has better structural advantages than silicon nanowires and has a higher capacity retention capacity. In Experimental Example 2, the negative electrode material m-Si-12 prepared in 12 hours from mesoporous silicon has the best performance. The possible reasons are as follows:
[0084] (1) m-Si-12 has the expected mesoporous structure: The thin skeleton structure of m-Si-12 is similar to the expected mesoporous silicon structure, while the skeleton structures of m-Si-6 and m-Si-18 have changed, resulting in the collapse and blockage of the mesoporous structure.
[0085] (2) m-Si-12 has highly crystalline silicon: The silicon of m-Si-12 has highly crystalline properties. In contrast, the silicon crystal diffraction peak of m-Si-6 is weak, indicating that the 6-hour reduction time is not enough to completely convert amorphous silicon dioxide into highly crystalline silicon.
[0086] In summary, m-Si-12 performs better in maintaining the mesoporous structure and having highly crystalline silicon, so m-Si-12 has a higher capacity and better cycle performance.
[0087] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. A silicon negative electrode material, characterized in that: The silicon negative electrode material comprises a composite material composed of silicon and carbon, wherein the silicon and carbon are interpenetrated to form a continuous network structure, and the outer layer is coated with amorphous carbon.
2. A method for preparing a silicon negative electrode material as claimed in claim 1, characterized in that: The following steps are involved: S1, adding a soluble silicate solution into dilute hydrochloric acid to form a wet gel, then performing a hydrolysis reaction and a gelation reaction, and performing a solvent exchange on the obtained gelation system to obtain a mesoporous silica aerogel; S2, mixing mesoporous silica aerogel, magnesium powder and sodium chloride and heating them to react to obtain mesoporous silica; S3, impregnating the mesoporous silicon with high-temperature asphalt and then carbonizing it to obtain a bicontinuous Si / C composite negative electrode material; S4. A carbon source gas is introduced into the bicontinuous Si / C composite negative electrode material to obtain an outer layer amorphous carbon-coated silicon negative electrode material after reaction.
3. The preparation method according to claim 2, characterized in that: In step S1, the soluble silicate solution is a sodium silicate solution; the sodium silicate solution is obtained by stirring a sodium silicate aqueous solution having a mass fraction of 35 to 45% and deionized water at room temperature until the mixture is uniformly mixed; Preferably, the volume ratio of the sodium silicate aqueous solution to deionized water is 1:1 to 1:2; further preferably, the volume ratio of the sodium silicate aqueous solution to deionized water is 3:4; Preferably, the volume ratio of the sodium silicate aqueous solution, deionized water and dilute hydrochloric acid is 2-4:3-5:4-6; further preferably, the volume ratio of the sodium silicate aqueous solution, deionized water and dilute hydrochloric acid is 3:4:5; The concentration of the dilute hydrochloric acid is 1-5 mol / L; more preferably, the concentration of the dilute hydrochloric acid is 3 mol / L.
4. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S1, the reaction temperature of the hydrolysis reaction and the gelation reaction are both 55-75°C, and the reaction time is both 1.5-2.5h; preferably, the reaction temperature of the hydrolysis reaction and the gelation reaction in S1 are both 65°C, and the reaction time is both 2h; Preferably, a standing reaction is required after the gelation reaction; the temperature of the standing reaction is 55-75°C, and the reaction time is 22-26h; further preferably, the temperature of the standing reaction is 65°C, and the reaction time is 24h. Preferably, the solvent used in the solvent exchange is ethanol; more preferably, the solvent exchange needs to be performed 4 to 6 times, each time interval is 22 to 26 hours; more preferably, the solvent exchange needs to be performed 5 times, each time interval is 24 hours; Preferably, the drying method is supercritical drying.
5. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S2, the mass ratio of the mesoporous silica aerogel, magnesium powder and sodium chloride is 0.8-1.2:0.8-1.2:8-12; Preferably, the weight ratio of the mesoporous silica aerogel, magnesium powder and sodium chloride in S2 is 1:1:
10.
6. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S2, the temperature of the heating reaction is 620-660°C, and the reaction time is 6-18 hours; preferably, the temperature of the heating reaction in S2 is 650°C, and the reaction time is 12 hours; Preferably, the heated product needs to be removed from the mixture, cleaned and vacuum dried in sequence to obtain mesoporous silicon; Wherein, the heated product is immersed in a 3M hydrochloric acid solution to remove by-products; Preferably, the vacuum drying temperature is 75-85°C; further preferably, the vacuum drying temperature is 80°C.
7. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S3, the mass ratio of the mesoporous silicon to the high-temperature asphalt is 0.8-1.2:0.8-1.2; preferably, the mass ratio of the mesoporous silicon to the high-temperature asphalt in S3 is 1:
1.
8. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S3, the heating treatment is divided into a first heating treatment and a second heating treatment; Before the heating treatment, argon gas is introduced at a flow rate of 1.4 to 3 L / min; The first heating treatment is to heat the graphene to 250-350°C at a heating rate of 3-8°C / min and keep the temperature for 20-40min, so that the molten graphene can penetrate into the pores; the second heating treatment is to continue heating to 500-800°C at a heating rate of 3-8°C / min, so that the graphene can be pyrolyzed into carbon, and the temperature can be kept for 0.5-2h; Preferably, the first heating treatment is to heat up to 300°C at a heating rate of 5°C / min and keep warm for 30 minutes; the second heating treatment is to continue heating to 700°C at a heating rate of 5°C / min and keep warm for 1 hour.
9. The method for preparing a silicon negative electrode material according to claim 2, characterized in that: In step S4, the carbon source gas is selected from one or two of methane, ethylene or acetylene gas (purity 99.99%).
10. Use of the silicon negative electrode material prepared by the preparation method according to any one of claims 2 to 9 in lithium ion batteries.
Citation Information
Patent Citations
Preparation method of lithium ion battery porous silicon carbon composite negative material
CN102709565A
Preparation method for silicon dioxide / carbon nano composite aerogel negative electrode material of lithium ion battery
CN105742600A
Preparation method of silicon carbon composite material and application thereof used as lithium ion battery negative electrode material
CN107768618A
Preparation method of porous silicon carbon composite anode material
CN108493412A
Preparation method of silicon dioxide plural gel and three-dimensional porous silicon anode material utilizing same
CN108565441A
